Nutritional and exercise interventions to improve conception in women suffering from obesity and distinct nosological entities - Gitsi, Evdoxia; Livadas, Sarantis; Argyrakopoulou, Georgia (Frontiers in Endocrinology, 2024)
Infertility among women, particularly those living with obesity, presents a multifaceted challenge with implications for reproductive health worldwide. Lifestyle interventions, mainly focusing on weight loss, have emerged as promising strategies to improve fertility outcomes in this population. This review aims to explore the effectiveness of various lifestyle interventions, encompassing dietary modifications and exercise regimens, in enhancing fertility outcomes among women with obesity and associated conditions such as polycystic ovary syndrome, congenital adrenal hyperplasia, type 2 diabetes mellitus, premenopause, hypothyroidism and eating disorders. Methodology of study search encompass a broad spectrum, ranging from interventions targeting weight management through slow or rapid weight loss to dietary approaches emphasizing whole food groups, specific nutrients, and dietary patterns like low-carbohydrate or ketogenic diets, as well as the Mediterranean diet. By synthesizing existing findings and recommendations, this review contributes to the understanding of lifestyle interventions in addressing infertility, with an emphasis on the population of women of reproductive age with excess weight and known or unknown infertility issues, while promoting their integration into clinical practice to optimize reproductive health and overall well-being.